Algae - a Super Food and a Panacea for Health and Nutritional Issues of the World - Achankunju , Jackson; Dev , Satyanarayan; Perumal, U. Elaya (Emerging Challenges in Agriculture and Food Science Vol. 8, 2023)
Algae produce a nutrient dense biomass by photosynthesis. Algal biomass is composed of a wide range of invaluable biomolecules including digestible proteins; lipids; carbohydrates; pigments, vitamins, antioxidants and trace elements. Algae could serve as an affordable, natural and nutrient rich food constituent or supplement for human and feed for animals. Though algae have been used as a source of human food for ages by certain communities, they are yet not accepted as food by the majority. The unsolved issues of human survival such as hunger and malnutrition, drive the search for new, accessible and affordable sources of food. Many species of algae yet remain as an untapped resource for innovative food products or food supplements that would mitigate the nutritional deficiencies of mankind and enhance the global health status. More research involving in vivo investigations along with realistic physiological studies would be required for establishing many species of algae as a sustainable resource for nutraceuticals and nutritious foods.